Preparation and Characterization of Ag Nanoparticle/SiO2 Composite for Optical Application - Aphisit Manivong; Wanichaya Mekprasart; Kanokthip Boonyarattanakalin; Krisana Chongsri; Wisanu Pecharapa (My University, 2023)
Abstract A facile method to fabricate volumetric light-guide plate (LGP) by micro-nanostructure of Ag/SiO 2 composite was presented in this study. The Ag NPs/SiO 2 composite were first prepared from a mixture of yellowish-brown Ag NPs colloids and SiO 2 powder by electrostatic self-assembly method. Its chemical and physical properties were investigated by scanning transmission microscopy (TEM), scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDX). The small particles (Ag/SiO 2 composite) in the LGP could produce multiple scattering effect with different size of micro-nanoparticles, which could improve the light-scattering performance of the LGP. The effective light scattering of the material into LGP was obtained from the increased amount of the particles. Meanwhile, surface plasmon resonance effect of Ag NPs also improves the performance of LGP, which could be further applied to design device in optical application. In additional, optical properties and light scattering mechanism of the Ag NPs/SiO 2 composite in the LGP are discussed and presented.
Keywords: Characterization; Nanomaterials and Printing Technologies